Ionic liquids as an enabling tool to integrate reaction and separation processes. Issue 24 (5th November 2019) - Villa, Rocio; Alvarez, Elena; Porcar, Raul; Garcia-Verdugo, Eduardo; Luis, Santiago V.; Lozano, Pedro
Abstract : This tutorial review highlights representative examples of ionic liquid (IL)-based (bio)catalytic systems integrating reaction and separation, as a tool for the development of sustainable chemical processes ( e.g. IL/scCO2 biphasic reactors, membrane reactors, nanodrop systems, microfluidic devices, supported IL phases, sponge-like ILs, etc .). Abstract : The development of advanced processes able to directly provide pure products by integrating chemical transformations, product separation and recovery and reuse of solvent and catalytic phases by straightforward and smart approaches is a key feature to build green chemical processes. The unique properties of ionic liquids (ILs), one of the key enabling technologies, can lead, when combined with (bio)catalysts, to amazing synergies not only improving the catalytic efficiency ( i.e. improved activity and enantioselectivity, enhanced stability, etc .), but also allowing the design of smart approaches for product separation ( e.g. IL/scCO2 biphasic reactors, membrane reactors, nanodrop systems, microfluidic devices, supported IL phases, sponge-like ILs, etc .), incorporating the full recovery and reuse of the catalyst and the IL phase. This tutorial review highlights representative examples of IL-based systems integrating reaction/separation as a tool for the development of sustainable chemical processes leading to clean and pure chemical products.